(untitled) (Editora Impacto Científico, 2025)
Total edentulism is a debilitating condition that severely affects masticatory function and quality of life, especially in the elderly. Rehabilitation with implant-supported prostheses has overcome the limitations of conventional dentures, but faces anatomical challenges, such as bone atrophy in the posterior maxilla. This narrative review analyzes current rehabilitation strategies. In the mandible, implant-retained overdentures are effective, with telescopic attachment systems offering high satisfaction and peri-implant health. For the atrophic maxilla, graftless approaches have gained prominence: short implants demonstrate survival rates comparable to those of grafted areas, reducing morbidity; prostheses with distal cantilevers functionally rehabilitate the posterior region, despite a higher risk of mechanical complications; and zygomatic implants are the standard solution for extreme atrophy, with high success rates, especially with modern surgical techniques that minimize sinus complications. DOI: https://doi.org/10.56238/edimpacto2025.093-004